ASPECTS OF THE MCMASTER INTENSE POSITRON BEAM FACILITY (MIPBF) - Li, Peihai (My University, 2015)
The McMaster Intense Positron Beam Facility (MIPBF) is a project based on the McMaster Nuclear Reactor (MNR) that aims to set up the first intense positron beam in Canada. The final intensity of the moderated positron flux is expected to be 109/s, which will make the positron beam one of the most intense ones in the world. A general review of intense beams, including the linac-based positron beams and reactor-based positron beams, applied around the world will be given. The details of the MIPBF project, especially the defect characterization system will be discussed in the thesis. A beam system for out of core test of the defect characterization system has been constructed. Components in spectrum acquisition and analysis system have been calibrated and tested. A simple coincidence Doppler broadening spectroscopy system has been set up. An electron beam for simulating the positron beam has been tested successfully. The experiments on beam transportation will be discussed. A new positron source and a moderator have been installed in the beam system. The operational procedures and instructions of the beam system will be provided.